AGEING AND HEALTH: A COMPARATIVE STUDY OF RURAL AND URBAN AGED HEALTH STATUS IN BAYELSA STATE, NIGERIA - Endurance Uzobo; Oluwatosin Abigail Dawodu (European Scientific Journal, ESJ, 2015)
This study investigates Ageing and Health: A Comparative Study of Rural and Urban Aged Health Status in Bayelsa State, Nigeria. The study after reviewing literatures relating to the study made use of the life course theory as the theoretical base to back up the study. The survey study, made use of 216 sampled sizes drawn from both the rural and urban centres of Bayelsa state. The questionnaire served as the primary source of data collection. Data collected from the field were analysed using tables, mean, standard deviation and the Z-test for the testing of hypotheses. Findings from the study revealed that the aged in the rural areas suffer poorer health conditions than the aged in urban centres due to reasons ranging from poverty to unavailability of health care facilities. Recommendations like social support for the elderly, creating special wards for the elderly, etc. were made in the study by the researcher.